Ku-gaa-gii pimitizi-win, the COVID-19 cohort study of people experiencing homelessness in Toronto, Canada: a study protocol. Issue 8 (5th August 2022) - Richard, Lucie; Nisenbaum, Rosane; Liu, Michael; McGeer, Allison; Mishra, Sharmistha; Gingras, Anne-Claude; Gommerman, Jennifer L; Sniderman, Ruby; Pedersen, Cheryl; Spandier, Olivia; Jenkinson, Jesse I R; Baral, Stefan; et al.
Abstract : Introduction: Initial reports suggest people experiencing homelessness (PEH) are at high risk for SARS-CoV-2 infection and associated morbidity and mortality. However, there have been few longitudinal evaluations of the spread and impact of COVID-19 among PEH. This study will estimate the prevalence and incidence of COVID-19 infections in a cohort of PEH followed prospectively in Toronto, Canada. It will also examine associations between individual-level and shelter-level characteristics with COVID-19 infection, adverse health outcomes related to infection and vaccination. Finally, the data will be used to develop and parameterise a mathematical model to characterise SARS-CoV-2 transmission dynamics, and the transmission impact of interventions serving PEH. Design, methods and analysis: Ku-gaa-gii pimitizi-win will follow a random sample of PEH from across Toronto (Canada) for 12 months. 736 participants were enrolled between June and September 2021, and will be followed up at 3-month intervals. At each interval, specimens (saliva, capillary blood) will be collected to determine active SARS-CoV-2 infection and serologic evidence of past infection and/or vaccination, and a detailed survey will gather self-reported information, including a detailed housing history. To examine the association between individual-level and shelter-level characteristics on COVID-19-related infection, adverse outcomes, and vaccination, shelter and healthcare administrative data will be linked to participant study data. Healthcare administrative data will also be used to examine long-term (up to 5 years) COVID-19-related outcomes among participants. Ethics and dissemination: Ethical approval was obtained from the Unity Health Toronto and University of Toronto Health Sciences Research Ethics Boards (# 20-272). Ku-gaa-gii pimitizi-win was designed in collaboration with community and service provider partners and people having lived experience of homelessness. Findings will be reported to groups supporting Ku-gaa-gii pimitizi-win, Indigenous and other community partners and service providers, funding bodies, public health agencies and all levels of government to inform policy and public health programs.